Structure-Guided Design of a Highly Selective Glycogen Synthase Kinase-3ß Inhibitor: A Superior Neuroprotective Pyrazolone Showing Antimania Effects - Chen, W.; Gaisina, I.; Gunosewoyo, Hendra; Malekiani, S.; Hanania, T.; Kozikowski, A. (Wiley-VCH Verlag GmbH & Co. KGaA, 2011)
A new craze! A new chemical scaffold, namely a staurosporine-like molecule (shown) possessing a pyrazolone core, was found to be highly selective for glycogen synthase kinase 3 over a group of other homologous kinases, including typical cyclin-dependent kinases. This compound gave an impressive dose–response curve for neuroprotection in the homocysteic acid model of oxidative stress (graph shown), and furthermore, blocked chemically induced mania-like effects in mice.